1984
DOI: 10.1073/pnas.81.20.6496
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolic effects of hyperglycemia in murine radiation-induced fibrosarcoma: a 31P NMR investigation.

Abstract: The hyperglycemia-induced in vivo metabolic changes pro4uced in subcutaneous murine RIF-1 tumors, grown on female C3H/Anf mice, were examined with 31P surface-coil NMR. Serum glucose levels were elevated 4-fold by bolus intrape& toneal injection of 0. Hyperglycemia, an increase in the serum glucose concentration ([Glc]b), has been reported to selectively enhance the thermal sensitivity of tumors and thereby represents a useful adjuvant of hyperthermia in the treatment of cancer ;1-5).The side effects associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Although 31 P MRS was not available to measure the pHi, the pH modulation in the presence of amiloride and DIDS revealed slight but significant anti-tumour responses, indicating a reduction of the intracellular pH ≤ 6.5 for at least certain tumour areas and sufficient time to induce cell kill (Rotin et al, 1987;Newell and Tannock, 1989). This level of acidification is in reasonable agreement with a calculated pHi of about 6.6, assuming full equilibration of protons from the extracellular volume of 30% of RIF-1 tumours (Evelhoch et al, 1984) at pHe 6.2. Variation in the schedule of the combined treatment with melphalan (Table 5) indicated that an effective low intratumoral pH persisted for at least 6 h after the start of the treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Although 31 P MRS was not available to measure the pHi, the pH modulation in the presence of amiloride and DIDS revealed slight but significant anti-tumour responses, indicating a reduction of the intracellular pH ≤ 6.5 for at least certain tumour areas and sufficient time to induce cell kill (Rotin et al, 1987;Newell and Tannock, 1989). This level of acidification is in reasonable agreement with a calculated pHi of about 6.6, assuming full equilibration of protons from the extracellular volume of 30% of RIF-1 tumours (Evelhoch et al, 1984) at pHe 6.2. Variation in the schedule of the combined treatment with melphalan (Table 5) indicated that an effective low intratumoral pH persisted for at least 6 h after the start of the treatment.…”
Section: Discussionsupporting
confidence: 86%
“…70% of the signal in bulk pH measurement is from intracellular sources and 30% from extracellular ones. Hence, a large enough difference in extracellular pH would still be reflected in the signal (50)(51)(52). To avoid contamination of the signals, localized voxels of >125 mm 3 were used rather than global scans, which meant that we could not compare the tumors to normal mammary glands, which are too small in volume.…”
Section: Resultsmentioning
confidence: 99%
“…While not a direct measure of blood flow, energy metabolism is strongly coupled to blood flow and 31 PMR spectra are therefore very sensitive to changes in blood flow. Previous studies have demonstrated that the modulation of tumor blood flow through radiation, chemotherapy as well as thermal therapy is associated with rapid and predictable changes in the NTP/P i ratio(43-46). This relationship is underscored by the robust and congruent changes in tumor blood flow and NTP/P i ratio associated with administration vasoactive agents(47, 48).…”
Section: Discussionmentioning
confidence: 99%